Tissue engineering approaches for lymphedema: biomaterial innovations and clinical potential - Deshpande, Pooja; Dornbrand-Lo, Maya; Phondge, Varoon; Kelly, Patrick; Wong, Alex K. (Frontiers in Cell and Developmental Biology, 2025)
The lymphatic system plays a critical role in maintaining fluid balance and immune regulation. Lymphedema, and other lymphatic disorders, highlight the need for advanced therapeutic approaches, including tissue engineering. This review examines the latest developments in artificial lymphatic tissue engineering, focusing on scaffold materials, lymphangiogenic factors, and regenerative strategies to replicate the intricacy of lymphatic vessels and nodes. We conducted a thorough literature review of current practices and applications in lymphatic tissue engineering. Findings show that biomaterials such as hydrogels, decellularized matrices, and synthetic polymers provide effective scaffolds for lymphatic endothelial cell proliferation and lymphangiogenesis. Advances in growth factor delivery and stem-cell based therapies have further enhanced the viability of engineered lymphatic tissues. Despite promising progress, challenges in achieving functional replication of lymphatic structures and clinical translation of research remain. Ongoing research must address scaffold biocompatibility, optimized growth factor targeting, and scalable production to advance therapeutic options for lymphatic disorders. This review underscores the potential for transformative patient outcomes through innovative bioengineering solutions.